2012
DOI: 10.3138/ijfab.5.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biocrossings: Indian egg donors and surrogates in the globalized fertility market

Abstract: A growing number of infertile couples and other individuals desiring children are seeking to fulfill their desire for parenthood transnationally through the use of donor gametes and a surrogate. The number of “fertility tourists” from developed countries to low-income countries is growing phenomenally. Indian women, too, are participating as (re)producers in these “biocrossings,” turning India into the surrogacy outsourcing capital of the world in the globalized bioeconomy of assisted reproduction. I argue for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…Reflecting the focus on and concern for sustainability, the literature on the bioeconomy also contains tensions and critical voices to the focus on economic growth and commercialisation in the bio-technology and in the bio-resource visions. In the literature on health there are several contributions that criticise the commercialisation of bio-resources in areas such as trade in various forms of human tissues (examples of such criticism include questioning trade in cord-blood [62][63][64][65], oocytes [66][67][68], foetal tissue [69], stem cells [70], femoral head [71], or blood [72,73]. Examples of topics that are discussed are the ethics of commercialisation of bioresources [74], safety in blood supply [72], inequalities in access to bio-resources [75], or moral dilemmas of surrogacy [67]).…”
Section: The Bio-ecology Visionmentioning
confidence: 99%
“…Reflecting the focus on and concern for sustainability, the literature on the bioeconomy also contains tensions and critical voices to the focus on economic growth and commercialisation in the bio-technology and in the bio-resource visions. In the literature on health there are several contributions that criticise the commercialisation of bio-resources in areas such as trade in various forms of human tissues (examples of such criticism include questioning trade in cord-blood [62][63][64][65], oocytes [66][67][68], foetal tissue [69], stem cells [70], femoral head [71], or blood [72,73]. Examples of topics that are discussed are the ethics of commercialisation of bioresources [74], safety in blood supply [72], inequalities in access to bio-resources [75], or moral dilemmas of surrogacy [67]).…”
Section: The Bio-ecology Visionmentioning
confidence: 99%
“…Reproductive biocrossings, as these travels are labeled by Gupta,14 are most likely to occur when access to reproductive care is restricted in one's home country. Travelers cite such motivating factors as limitations on the legality of (anonymous) egg donation and ART for single women, unmarried couples, or same sex couples, age limitations on accessing fertility treatments, costs associated with egg donation, shortage of donor eggs or shortage of donors with specific characteristics, and extensive delays in access to in vitro fertilization (IVF) treatment with donor eggs.…”
Section: Legal Inconsistencies Encourage Cross-national Travel For Trmentioning
confidence: 99%
“…Travelers cite such motivating factors as limitations on the legality of (anonymous) egg donation and ART for single women, unmarried couples, or same sex couples, age limitations on accessing fertility treatments, costs associated with egg donation, shortage of donor eggs or shortage of donors with specific characteristics, and extensive delays in access to in vitro fertilization (IVF) treatment with donor eggs. 12,14,15 Reproductive travel to circumvent legal restrictions on access to ART using egg donation may involve travel to areas of equal or higher economic conditions. Few jurisdictions have collected verifiable data on cross-national travel for fertility care, yet a survey by the International Committee Monitoring Assisted Reproductive Technologies in 2006 suggested that many European patients travel to Spain for fertility care, including sperm and oocyte donation.…”
Section: Legal Inconsistencies Encourage Cross-national Travel For Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Should there be a limit on the number of offspring/number of donations? Some opinions on gamete compensation suggest people will take advantage of the opportunity to oversell themselves for the sake of economic return (5). If the concern about compensation rests on the idea that donations would be overdone, the restriction could be on the number of times one can donate gametes, not on whether one can be paid for the service (5).…”
mentioning
confidence: 99%